Geotechnical behavior of a tropical residual soil contaminated with soap solution (2015)
Tropical soils are soils that exhibit physical, chemical, mineralogical and mechanical characteristics that differ from those of temperate zone soils as a result of factors such as weather, humidity and other conditions of the tropics. These characteristics and the anthropogenic contamination of the environment are the subject of the present study, which aims to analyze a soil of tropical residual origin located in the municipality of Guarne - Antioquia (Colombia). Laboratory tests, some of which are more adequate to characterize this type of soil than classical methods (miniature compacted tropical classification, suction, the pinhole test, breakdown, the collapse index, X-ray diffraction, scanning electron microscopy) are performed on samples in their natural state and samples contaminated with a soap solution to establish the differences between the geotechnical characteristics of this soil under both conditions. Subsequently, the influence of the contaminant on the soil’s properties is discussed.